GENDER-SPECIFIC METHOD OF TEACHING A FOREIGN LANGUAGE AT HIGHER EDUCATIONAL ESTABLISHMENTS - KOVAL, Svitlana Mykolaivna (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2018)
Introduction. The article deals with the problem of gender-specific method implementation into the process of learning a foreign language in a higher educational establishment. A comprehensive study of gender issues in the field of education is particularly important and relevant. Despite the large number of scientific studies devoted to the gender perspective in education, and the existence of the shaped theoretical framework concerning gender and the development of higher education, a number of relevant aspects of studying the methodology of teaching a foreign language to students of higher educational institutions of Ukraine from the standpoint of a gender perspective requires a more detailed interpretation. The purpose of the article is to characterize the methodology of teaching a foreign language through the prism of gender characteristics of a student personality in higher educational institutions of Ukraine. Results. By organizing the educational process based on the gender approach and introducing a gender approach to the education of boys and girls in higher educational institutions, it is especially important to take into account the psychological, neuropsychological characteristics of students of different sex and their cognitive indicators. Providing a high school of a new type with competent teachers, one should be guided by the professional skills of a teacher, by his or her personal qualities, gender dominants. Originality. Obvious differences in cognitive activity, motivation for learning, and behavior are known to be present between the opposite sex. Men are researchers by nature, so the method of micro-discovers in classrooms is an important guarantee of success for them. In female groups foreign language classes should be structured by dividing themes into blocks. It is important for a tutor to teach female students to advocate and prove their point in a foreign language. Conclusion. Modern pedagogical science and practice do not always take into account gender as an important characteristic of a student. The task of the educational process based on the gender approach is to maximize the full potential of both boys and girls so that each of them can succeed in the future. The result of the work is the creation of a gender-friendly educational environment, which is made through the methodical influence of the educational process on the student as a person in general, on a young man and on a girl as a subject of education in particular.